Hereditary and Familial Traits in Urological Cancers and Their Underlying Genes - Hemminki, Kari; Kiemeney, Lambertus A; Morgans, Alicia K; Ranniko, Antti; Pichler, Renate; Hemminki, Otto; Culig, Zoran; Mulders, Peter; Bangma, Chris H (European urology open science, 2024)
UNLABELLED: Early recognition of hereditary urological cancers may influence diagnostic and therapeutic decision-making, and potentially alter the fate of patients and family members. Here, we introduce readers to the current knowledge on germline genetic testing and clinical practice in prostate, bladder, renal, and testicular carcinoma. Considering all urological cancer patients, routine inquiries about familial cancer history should become a standard practice in clinical settings. If suspicion arises, patients can opt for two avenues: referral to genetic counseling or undergoing genetic tests after consultation with the treating urologist. PATIENT SUMMARY: Tumors of the urogenital tract (prostate, kidney, bladder, and testes) can sometimes be related to genetic mutations that are present in all the cells of the body. Such mutations can be inherited and run in families. Therefore, it is relevant to obtain information on the incidence of all cancers in the family history. The information obtained may initiate genetic testing, leading to the identification of mutations that are related to cancer in the current or next generation. In addition, these mutations may offer alternative treatment options for patients.
Keywords: Genetic; Renal cancer; Syndromes; Prostate cancer; Hereditary cancer; Urothelial tract cancer; Testicular cancer; Germline testing